The witch's walking stick - Meddaugh, Susan (Boston : Houghton Mifflin Co., 2005)
When a witch loses her magic walking stick, which has been used over the years to grant hundreds of miserable wishes, she tricks a young girl into finding and returning it, with unexpected results.
"Walter Lorraine books."
87157
Keywords: Witches -- Fiction; Wishes -- Fiction; Magic -- Fiction; Witches -- Juvenile fiction; Wishes -- Juvenile fiction; Magic -- Juvenile fiction